Impact of information and communication overload syndrome on the Performance of Students - Mariamdaran Chethiyar, Saralah Devi; Asad, Muzaffar; Ud Kamaluddin, Mohammad Rahim; Ali, Ahsan; Bait Ali Sulaiman, Mohammed Ali (Opción, 2019)
The purpose of this study is to analyze the impact of information and communication overload syndrome. This study follows a quantitative methodology and will adopt a survey research design. The survey method will allow the researcher to gather quantitative data and analyze it using descriptive and inferential statistics. The results of this study revealed that there are significant differences among the performance of students on the basis of gender differences. In conclusion, both the participants’ males and females are negatively affected by information and communication overload syndrome